PENGARUH PENGGUNAAN CHATGPT TERHADAP EFIKASI DIRI MAHASISWA PROGRAM STUDI PERPUSTAKAAN DAN ILMU INFORMASI UNIVERSITAS NEGERI PADANG - Herata, Hagi; Gustina Erlianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the massive use of artificial intelligence, specifically ChatGPT, among students. Although offering efficiency, concerns arise regarding its impact on students' belief in their own capabilities (self-efficacy). This study aims to measure the influence of ChatGPT usage on the self-efficacy of students in the Library and Information Science Program at Universitas Negeri Padang. This is a quantitative descriptive study with a population of 91 students from the class of 2021, and a sample of 75 respondents selected using simple random sampling. Data analysis used simple linear regression. The results showed a positive and significant influence of ChatGPT usage on self-efficacy with a significance value of 0.000 < 0.05 and t-count (5.566) > t-table (1.665). The contribution of influence (R Square) is 29.8%, while 70.2% is influenced by other factors. It is concluded that appropriate use of ChatGPT can support the increase of students' self-confidence.